Effectiveness of a home-environmental intervention package and an early child development intervention on child health and development in high-altitude rural communities in the Peruvian Andes: a cluster-randomised controlled trial - Néstor Nuño; Daniel Mäusezahl; Jan Hattendorf; Hector Verastegui; Mariela Ortiz; Stella M. Hartinger (BMC, 2022)
Abstract Background Unsafe drinking water, poor sanitation and hygiene, exposure to household air pollution and low cognitive and socio-emotional stimulation are risk factors affecting children in low- and middle-income countries. We implemented an integrated home-environmental intervention package (IHIP), comprising a kitchen sink, hygiene education and a certified improved biomass cookstove, and an early child development (ECD) programme to improve children´s health and developmental outcomes in the rural high-altitude Andes of Peru. Methods We conducted a one-year cluster-randomised controlled trial among 317 children < 36 months divided into 4 arms (IHIP + ECD, IHIP, ECD, and Control) and 40 clusters (10 clusters per arm). ECD status (socio-emotional, fine and gross motor, communication, cognitive skills, and an overall performance) measured with the Peruvian Infant Development Scale and the occurrence of self-reported child diarrhoea from caretakers were primary outcomes. Secondary outcomes included the occurrence of acute respiratory infections and the presence of thermo-tolerant faecal bacteria in drinking water. The trial was powered to compare each intervention against its control arm but it did not allow pairwise comparisons among the four arms. Primary analysis followed the intention-to-treat principle. For the statistical analysis, we employed generalised estimating equation models with robust standard errors and an independent correlation structure. Results We obtained ECD information from 101 children who received the ECD intervention (individually and combined with IHIP) and 102 controls. Children who received the ECD intervention performed better in all the domains compared to controls. We found differences in the overall performance (64 vs. 39%, odd ratio (OR): 2.8; 95% confidence interval (CI): 1.6-4.9) and the cognitive domain (62 vs 46%, OR: 1.9; 95% CI: 1.1-3.5). Data analysis of child morbidity included 154 children who received the IHIP intervention (individually and combined with ECD) and 156 controls. We recorded 110,666 child-days of information on diarrhoea morbidity and observed 1.3 mean episodes per child-year in the children who received the IHIP intervention and 1.1 episodes in the controls. This corresponded to an incidence risk ratio of 1.2 (95% CI: 0.8-1.7). Conclusions Child stimulation improved developmental status in children, but there was no health benefit associated with the home-environmental intervention. Limited year-round access to running water at home and the possible contamination of drinking water after boiling were two potential factors linked to the lack of effect of the home-environmental intervention. Potential interactions between ECD and home-environmental interventions need to be further investigated. Trial registration: ISRCTN, ISRCTN-26548981. Registered 15 January 2018-Retrospectively registered, https://doi.org/10.1186/ISRCTN26548981 . Graphical abstract